2013
DOI: 10.1186/1471-2458-13-901
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Brucellainfection and malaria among Abattoir workers in Kampala and Mbarara Districts, Uganda

Abstract: BackgroundBrucellosis is among the most widespread zoonotic infections estimated at 14% in Uganda. A cross-sectional study was conducted to estimate the sero-prevalence, risk factors of Brucella infection and malaria among abattoir workers.MethodsA survey was conducted among 232 abattoir workers in main abattoirs of Kampala and Mbarara districts in February 2007. A pre-tested questionnaire captured socio-demographic and occupational data. Brachial vein blood was tested for Brucella using Microplate Agglutinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 11 publications
(25 reference statements)
5
37
3
1
Order By: Relevance
“…The consequences are widespread incidences of human brucellosis (Faye et al, 2005;Swai and Schoonman, 2009;Kunda et al, 2010). Recent reports by Nabukenya et al (2013) indicate a seroprevalence of 7-10% among abattoir workers in Kampala and Mbarara. Indigenous cattle in Uganda constitute approximately 93.3% of the national herd and have adjusted to local agro-ecological conditions under the stewardship of rural smallholder farmers (MAAIF/UBOS, 2009;Balikowa, 2011).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The consequences are widespread incidences of human brucellosis (Faye et al, 2005;Swai and Schoonman, 2009;Kunda et al, 2010). Recent reports by Nabukenya et al (2013) indicate a seroprevalence of 7-10% among abattoir workers in Kampala and Mbarara. Indigenous cattle in Uganda constitute approximately 93.3% of the national herd and have adjusted to local agro-ecological conditions under the stewardship of rural smallholder farmers (MAAIF/UBOS, 2009;Balikowa, 2011).…”
Section: Introductionmentioning
confidence: 93%
“…Its economic burden among pastoral and smallholder livestock farmers results into reduced success of poverty reduction initiatives through loss of productivity and income (WHO, 2006;MAAIF, 2010). Cattle brucellosis is primarily caused by Brucella abortus organisms (Radostits et al, 2000), which occur in high concentration in placental membranes and fluids at parturition, aborted fetuses, unpasteurized dairy products consequently acting as sources of infection to other susceptible livestock and humans (Nabukenya et al, 2013;Racloz et al, 2013;Ducrotoy et al, 2014). Reproductive failure, lost milk yields and restrictions to lucrative markets (Mangen et al, 2002) comprise the main losses incurred due to cattle brucellosis.…”
Section: Introductionmentioning
confidence: 98%
“…A recent study among abattoir workers in Uganda reported a brucella seropositivity of 10% (95%CI: 6-16; n=232) 6 (Nabukenya et al, 2013). Symptoms of acute brucellosis caused by B. abortus and /or B. melitensis are flu-like and are highly non-specific.…”
Section: Corresponding Authormentioning
confidence: 99%
“…The disease is a zoonosis of worldwide distribution and a common cause of economic loss and ill health among animals and human populations. Although the incidence of brucellosis has decreased significantly in developed countries 6,8 , the disease remains a major public health threat in many developing countries including Uganda 7,8,9,10 .…”
Section: Corresponding Authormentioning
confidence: 99%
See 1 more Smart Citation